"A plea for recognition" Users' experience of humiliation during mental health care. (January 2019) - Husum, Tonje Lossius; Legernes, Elisa; Pedersen, Reidar
Abstract: Background: Studies reveal that users of mental health care services sometimes experience humiliation during care. These experiences may influence the users' recovery process and treatment satisfaction. Method: Thirteen informants with experience in mental health services were recruited for semi-structured interviews. Informants were recruited through collaboration with users' organisations. Modified text condensation was used for analysis of the qualitative data. Results: Users' experiences with humiliation in mental health care were sorted into three main themes. These are themes related to different perspectives between staff and users; themes related to violence of user autonomy; and experiences related to staff attitudes. Discussion: The service users in this study spoke about many different kinds of experiences with humiliation during care. It was a main finding that the feeling of not being recognized for one's own perception of the situation was experienced as a humiliation. This study is a contribution to a better understanding of the humiliation process between staff and users in mental health care services. The findings may be used to improve interaction between staff and users, improve quality of care and to prevent such experiences.